Impact of CD40 gene polymorphisms on the risk of cervical squamous cell carcinoma: a case-control study - Manning Zhu; Xiaoying Li; Yanan Feng; Tianshuang Jia; Songxue Li; Liping Gong; Shuang Dong; Xianchao Kong; Litao Sun (BMC Cancer, 2023)
Abstract Background Cervical cancer is the fourth most common cancer among women worldwide. Genome-wide association studies have revealed multiple susceptible genes and their polymorphisms for cervical cancer risk. Therefore, we aimed to investigate the correlation between single nucleotide polymorphisms (SNPs) of the CD40 gene and susceptibility to cervical squamous cell carcinoma (CSCC) in a population from the northeastern Han Chinese population. Methods The three SNPs (rs1800686, rs3765459, and rs4810485) of the CD40 gene were analyzed by multiplex polymerase chain reaction (PCR) combined with next-generation sequencing methods in 421 patients with CSCC, 594 patients with high-grade squamous intraepithelial lesions (HSIL), and 504 healthy females. Multivariate logistic regression analysis was used to analyze the potential relationship between CD40 gene polymorphisms and CSCC, or HSIL. Results Our research results showed the AA genotype of rs1800686 had a protective effect on CSCC in comparison to the GG genotype and AG+GG genotypes (AA vs. GG: p = 0.0389 and AA vs. AG+GG: p = 0.0280, respectively). After FDR correction, the results were still statistically significant (p = 0.0389 and p = 0.0389, respectively). Similarly, rs3765459 showed a reduced risk association for CSCC in the codominant and recessive models (AA vs. GG: p = 0.0286 and AA vs. AG+GG: p = 0.0222, respectively). Significant differences remained after FDR correction (p = 0.0286 and p = 0.0286, respectively). However, these differences were no longer significant after the Bonferroni correction. In addition, the genotypes for the rs4810485 polymorphisms were associated with parity of the patients with CSCC. The genotypes for the rs3765459 polymorphisms were significantly correlated with the D-dimer of the patients with CSCC. The 3 SNPs genotypes of the CD40 gene were closely related to the squamous cell carcinoma antigen (SCC) of the patients with HSIL. Conclusions The CD40 gene may play a role in the occurrence and development of CSCC.